2022
DOI: 10.3390/ma15030844
|View full text |Cite
|
Sign up to set email alerts
|

Direct Polypropylene and Polyethylene Liquefaction in CO2 and N2 Atmospheres Using MgO Light and CaO as Catalysts

Abstract: The polyolefin to lighter molecules reaction reduces the waste-plastic residues to produce fuels and valuable chemicals. Commercial MgO light and CaO were used as catalysts for the direct polyethylene and polypropylene liquefaction in N2 or CO2 atmospheres. The products were analyzed (ATR-FTIR, GC-FID/TCD, GC-FID, density, refractive index). The use of MgO light and CaO improved the conversion of propylene and ethylene to liquid products. In addition, low gaseous and solid products yields were obtained. A good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In all the liquids, the predominant product was gasoline, with yields between 57.7 % (MgO) and 45.3 % (HZSM-5 zeolite). Comparable gasoline yields were obtained by Hidalgo et al [36] using MgO and CaO. Also, Anene et al [52] in catalytic pyrolysis with zeolite at 460 ºC, obtained a similar gasoline yield (45.6 %).…”
Section: Effect Of Type Of Catalyst On Simulated Distillation Boiling...mentioning
confidence: 55%
See 2 more Smart Citations
“…In all the liquids, the predominant product was gasoline, with yields between 57.7 % (MgO) and 45.3 % (HZSM-5 zeolite). Comparable gasoline yields were obtained by Hidalgo et al [36] using MgO and CaO. Also, Anene et al [52] in catalytic pyrolysis with zeolite at 460 ºC, obtained a similar gasoline yield (45.6 %).…”
Section: Effect Of Type Of Catalyst On Simulated Distillation Boiling...mentioning
confidence: 55%
“…It is an effect that should be minimized since it inhibits the catalytic activity and increases the costs for the regeneration of the catalyst [59]. Xue et al [32] in the ex-situ catalytic pyrolysis at 600 ºC of PE, PP, PET, and PS over HZSM-5 zeolite or Hidalgo et al [36] in the catalytic pyrolysis of PE and PP over CaO and MgO reported similar coke deposition data. Other authors also reported gases, liquid, and solid yields, of catalytic pyrolysis of different plastics (see Table S1).…”
Section: Effect Of Type Of Catalyst On Product Yieldsmentioning
confidence: 95%
See 1 more Smart Citation